(untitled) (Research, Society and Development, 2022)
Drug interactions represent a major problem for public health and can lead to failure in drug therapy, which consequently increases public spending. Therefore, the objective of this study was to identify and analyze drug interactions in elderly people treated in the public health network of a municipality in Vale do Paraíba, São Paulo. A retrospective study was carried out with 120 individuals aged 60 years or over, who attended the public health network from January to March 2022. The analysis of the medical records of the elderly during the studied period revealed that women had a higher incidence of polypharmacy and of drug interactions compared to men. The drugs most used by the elderly were antihypertensives, followed by NSAIDs and hypoglycemic agents. Considering that elderly individuals present physiological changes that can alter the response to pharmacotherapy, it is essential to use intervention strategies to prevent undesirable events.